PERBEDAAN NILAI TRY OUT INTERNAL UJIAN KOMPETENSI BIDAN MATERI PERSALINAN SEBELUM DAN SESUDAH DIBERIKAN BIMBINGAN DENGAN SMALL GROUP DISCUSSION (SGD) - Lestari, Muji (NHM PRESS, 2022)
The national midwifery competency test passing rate is still low at 55% in 2018. The type of research is a quasi-experimental one with a one group pretest and posttest design. The population is 39 third-level students who are taking tryout exams and mentoring for competency exams with small group discussions in 2022. The sampling technique is total sampling. The average score before guidance with Small Group Discussion (SGD) was 45.77 and the average score after guidance was 85.69. There is a difference in the competency test scores for delivery materials before and after being given guidance with the Small Group Discussion (SGD) method with (p value 0.000 <0.05). It is recommended that frequent guidance is carried out so that student graduation in competency exams increases.